Extracellular Vesicles as a Translational Approach for the Treatment of COVID-19 Disease: An Updated Overview - Enrica Serretiello; Andrea Ballini; Annafrancesca Smimmo; Marina Acunzo; Mariarosaria Raimo; Stefania Cantore; Marina Di Domenico (Viruses, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused a global pandemic in the years 2020–2022. With a high prevalence, an easy route of transmission, and a long incubation time, SARS-CoV-2 spread quickly and affected public health and socioeconomic conditions. Several points need to be elucidated about its mechanisms of infection, in particular, its capability to evade the immune system and escape from neutralizing antibodies. Extracellular vesicles (EVs) are phospholipid bilayer-delimited particles that are involved in cell-to-cell communication; they contain biological information such as miRNAs, proteins, nucleic acids, and viral components. Abundantly released from biological fluids, their dimensions are highly variable, which are used to divide them into exosomes (40 to 150 nm), microvesicles (40 to 10,000 nm), and apoptotic bodies (100–5000 nm). EVs are involved in many physiological and pathological processes. In this article, we report the latest evidence about EVs’ roles in viral infections, focusing on the dual role of exosomes in promoting and inhibiting SARS-CoV-2 infection. The involvement of mesenchymal stromal/stem cells (MSCs) and MSC-derived EVs in COVID-19 treatment, such as the use of translational exosomes as a diagnostical/therapeutic approach, is also investigated. These elucidations could be useful to better direct the discovery of future diagnostical tools and new exosome-derived COVID-19 biomarkers, which can help achieve optimal therapeutic interventions and implement future vaccine strategies.